2017
DOI: 10.3390/en10030304
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Optimization of Surfactants in the Main and Vice Slug in Weak Base ASP Flooding

Abstract: Abstract:In ASP (Alkali-Surfactant-Polymer) flooding processes, surfactants help to enhance oil recovery by lowering the interfacial tension between the oil and water. However, due to the high cost of surfactants and the stability of the emulsion that varies with surfactant concentration, it is necessary to optimize the surfactant concentration in ASP flooding. In this study, we combined numerical simulation and physical experimental research to solve this problem. In order to screen for the optimal surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Diagram of the experimental process. 1-plunger pump; 2-beaker; 3-container; 4-water; 5-ASP solution; 6-pump sensor; 7-core holder; 8-base; 9-manual pump; 10-oven[14].…”
mentioning
confidence: 99%
“…Diagram of the experimental process. 1-plunger pump; 2-beaker; 3-container; 4-water; 5-ASP solution; 6-pump sensor; 7-core holder; 8-base; 9-manual pump; 10-oven[14].…”
mentioning
confidence: 99%
“…For instance, Alhaji et al [ 12 ] reported that the immobilized TiO 2 based photocatalytic process was able to efficiently remove more than 90% of COD from TPOME in 5 h of ultraviolet (UV) irradiation. Another study on photo-mineralization of TPOME using TiO 2 based photocatalysis demonstrated 78% COD removal from TPOME in 20 h under UV irradiation [ 21 ]. Nanostructured transition metal compounds, such as TiO 2 , with high surface-to-volume ratios are of particular scientific interest in the field of photocatalysis for environmental remediation.…”
Section: Introductionmentioning
confidence: 99%
“…For highly saline reservoirs, a large number of preflush slugs are required prior to chemical flooding to reduce the loss of chemical agents by highly saline water in the reservoir. Therefore, the use of various types of slugs before main agent injection can provide protection of chemical main agent [10][11][12]. Khan et al carried out the alternate injection scheme of high-viscosity slug and low-viscosity slug [13].…”
Section: Introductionmentioning
confidence: 99%